The Role of TPI Polonia's Class I Immigration Office in Fighting Transnational Crime: Human Smuggling and Trafficking - Jihan Savira; Rahul Ardian Fikri (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
Transnational crime, particularly human smuggling and trafficking, pose a serious threat to national and international stability. The increase in these crime cases in Indonesia shows the importance of the role of related agencies, such as Immigration. This study aims to analyze the role of the Class I Immigration Office of TPI Polonia in the prevention and control of transnational crimes. Using a sociological juridical approach, identifying and conceptualizing the law with real life, this study explores the challenges, successes, and steps that have been taken by the Immigration Office in dealing with this issue. The results of the study show that supervision of the issuance of travel documents, cooperation with related institutions, and socialization to the public are strategic steps in dealing with transnational crimes. However, obstacles such as data falsification and dishonesty of passport applicants remain challenges. To overcome this, the TPI Polonia Class I Immigration Office implements biometric technology, collaborates with the Population and Civil Registration Office (Disdukcapil), and conducts comprehensive interviews to ensure the authenticity of the applicant's data.